Quality of Trappist cheese from Croatian dairy plant - Anđela Merćep; Nevijo Zdolec; Željka Cvrtila Fleck; Ivana Filipović; Bela Njari; Mario Mitak; Lidija Kozačinski (Mljekarstvo)
The paper presents technological parameters, basic chemical composition and sensory evaluation, as well as the yield of 146 samples of Trappist cheese. In terms of water content in non-fat matter (56.36-58.31 %), Trappist cheese belongs to the group of semi-hard cheeses, and in terms of content of fat in dry matter (46.06-48.63 %), it belongs to the group of full-fat cheeses. In four cheese samples E. coli was determined within microbiological parameters, whereas other researched bacteria were not determined. Cheese has a shape of a symmetrical ring and it has a homogenous yellow color of protective coating. Mean mass value of one cheese ring is from 2.50 to 2.55 kg. The body of cheese has a homogenous light yellow color, which is brighter along the edges. The cheese holes have the size of a pea; they are bright and patterned over the whole surface of cross section. Consistency of cheese body is elastic, soft and interconnected. The cheese has mild, pure lactic and acidic taste and odor, and it is moderately salty. The results of sensory score show that even 91.78 % of cheese samples from experimental production can be assigned to the first quality class, whereas 8.22 % of samples belong to the second quality class.